PERANCANGAN EXPERT ADVISOR UNTUK TRADING OTOMATIS FOREX MENGGUNAKAN INDIKATOR STOCHASTIC DAN MACD PADA PLATFORM METATRADER 4 - Febryan Siaurence; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2022)
In the investment business, there is one investment business that is very popular with investors (traders) from other investments, the business is foreign currency exchange or what is often called foreign exchange or forex. Foreign Exchange (forex) is currently growing rapidly as one of the lucrative investment models, because with forex trading, investors have a high potential rate of return. In technical analysis, traders must be able to understand how to analyze trends to see market direction, see market momentum, and market liquidity. And not a few people who are lazy to learn or do not have the time to learn about all these analytical techniques. To overcome this problem, an Expert Advisor will be created using indicators to help novice traders, or traders who do not have time to analyze the market. By using Expert Advisors, it will be easier for traders to carry out transaction activities, where transactions will be carried out automatically according to what has been set by the trader without having to monitor each transaction continuously.